2023
DOI: 10.1007/s13201-022-01812-2
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the impacts of best management practices (BMPs) on pollution reduction in the Yarra River catchment, Australia

Abstract: Pollution of a watershed by different land uses and agricultural practices is becoming a major challenging factor that results in deterioration of water quality affecting human health and ecosystems. Sustainable use of available water resources warrants reduction of Non-Point Source (NPS) pollutants from receiving water bodies through best management practices (BMPs). A hydrologic model such as the Soil and Water Assessment Tool (SWAT) can be used for analyzing the impacts of various BMPs and implementing of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…This is not an atypical observation after BMP implementation in large (>1500 hectares) watersheds [23]. Modeling studies on large watersheds suggest that BMPs can be used to improve stream health, but 50% or more of watershed agricultural lands may need to be in BMPs to produce an observable effect [35,44]. If such a BMP implementation threshold is realistic and applicable to other large watersheds, the Whitewater River subwatersheds would need to at least double the areal coverage of BMPs before widespread improvements in stream health might be observed.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is not an atypical observation after BMP implementation in large (>1500 hectares) watersheds [23]. Modeling studies on large watersheds suggest that BMPs can be used to improve stream health, but 50% or more of watershed agricultural lands may need to be in BMPs to produce an observable effect [35,44]. If such a BMP implementation threshold is realistic and applicable to other large watersheds, the Whitewater River subwatersheds would need to at least double the areal coverage of BMPs before widespread improvements in stream health might be observed.…”
Section: Discussionmentioning
confidence: 98%
“…Even with new rules protecting stream riparia within the Whitewater watershed, total areal coverage of BMPs within the watershed likely will remain well below the possible 50% threshold [35,44] needed to truly protect stream systems from agricultural activities. Consequently, successful conservation management of watershed lands leading to improved stream health probably will require that future efforts focus on targeting BMPs within remaining problem areas and continuing maintenance of already existing BMPs.…”
Section: Discussionmentioning
confidence: 99%
“…Water quality problems due to total nitrogen (TN) and total phosphorus (TP) have become increasingly critical over the past few decades as a result of anthropogenic influences including point and non-point sources [1][2][3][4][5] resulting in serious water quality issues in lakes and reservoirs [6,7]. Several past studies reported that non-point sources from agricultural activities [8,9], especially due to the nutrient loading from the agricultural field, is one of the major contributors to water contamination in the United States [10][11][12].…”
Section: Introductionmentioning
confidence: 99%